Evaluasi Keamanan Sistem Informasi Akademik Menggunakan ISO 17799:2000 (Studi Kasus Pada Peguruan Tinggi X) - Mokodompit, Mona Permatasari; Nurlaela, Nurlaela (Universitas Diponegoro, 2016)
The security of an information system in a college is important since the strength of the security system will have a direct impact on the sustainability of the college. Academic information system in college is used in order to meet academic need, and therefore it’s security must be maintained in order to provide useful information for its users. Assessment standard for management information system information security that is internationally recognized is ISO 17799:2000. The research aims to evaluate the security academic information system of University X based on ISO 17799:2000 and to give recommendations to improve the security. This study was conducted using interview techniques, observation and giving questionnaires to managers and users of academic information system of university X. The questionnaire used is a closed questionnaire, which is a broke-down result of ten control clauses of ISO 17799:2000. Answers gathered were then assessed based on established criteria. The results showed that the academic information system security of University X included in the category of less secure, where the result presentation obtained was 59%. In order to increase the security, University X must give special attention to work on the security policy, security organization, personnel security, physical and environmental security, communication and operation management, access control and compliance.